Pr Procedure to optimize the performance of chemical laser (CCLs) using the genetic algorithm optimization - Ferhat , Mohammedi; Chaouki , Laggoun; Malika , Nouadji (International Journal of Applied Mathematical Research, 2024)
This work presents details of the study of the entire flow inside the facility where the exothermic chemical reaction process in the chemical laser cavity is analyzed. In our paper we will describe the principles of chemical lasers where flow reversal is produced by chemical reactions. We explain the device for converting chemical potential energy laser energy. We see that the phenomenon thus has an explosive trend. Finally, the feasibility and effectiveness of the proposed method is demonstrated by computer simulation.